2003
DOI: 10.5014/ajot.57.5.550
|View full text |Cite
|
Sign up to set email alerts
|

Fine Motor Activities in Head Start and Kindergarten Classrooms

Abstract: The higher mean percent of time spent in fine motor activities in kindergarten classrooms suggests a developmentally appropriate increase in fine motor demands. The percent of paper and pencil activity time the children engaged in substantially increased from Head Start to kindergarten. The findings describe a difference between the two environments, informing Head Start of the fine motor demands their graduates face in kindergarten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 9 publications
1
88
1
2
Order By: Relevance
“…Similar to findings of other studies (see Venetsanou & Kambas, 2010), the developmental delays our study population exhibited appeared to be the result of environmental factors (i.e., low SES and cultural values and practices). Thus, practicing developmentally appropriate motor and cognitive skills may have a positive effect on children's ability to participate in various daily activities (Mansour et al, 2003;Marr et al, 2003).…”
Section: Performance and Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to findings of other studies (see Venetsanou & Kambas, 2010), the developmental delays our study population exhibited appeared to be the result of environmental factors (i.e., low SES and cultural values and practices). Thus, practicing developmentally appropriate motor and cognitive skills may have a positive effect on children's ability to participate in various daily activities (Mansour et al, 2003;Marr et al, 2003).…”
Section: Performance and Participationmentioning
confidence: 99%
“…Similarly, Bronfenbrenner's (1979) Ecological Model of Child Development stresses that children's development is influenced by the quality of the relationships between the environment and the children. This perspective is supported by studies showing that children of low socioeconomic status (SES) had, or were at risk for, motor, cognitive, or social developmental delays affecting their school performance (Mansour et al, 2003;Marr, Cermak, Cohn, & Henderson, 2003). Studies have also shown that children from various countries and cultures differed with respect to the sequence and speed of their sensory-motor (Venetsanou & Kambas, 2010) and cognitive (Katz, Kizony, & Parush, 2002) development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Through the use of a dextrous grasp, the manipulation of objects and the enabling of multiple tool functions, the child can engage in play, self-care and school occupations (Henderson and Pehoski, 1995). Marr et al (2003) found that children in kindergarten spend nearly one half (46%) of their in-class time in some type of fine motor activity.…”
Section: Introductionmentioning
confidence: 99%
“…According to the researches, 30-60% of pre-school and primary school children spend 30-60% of their time at school with kinesthetic or fine motor activities, most often with writing (Marr, Cermak, Cohn & Henderson, 2003;McHale & Cermak, 1992). Handwriting, as a multifaceted perceptualmotor skill, is dependent on the development and integration of the individual's cognitive, perceptual and motor skill (Feder & Majnemer, 2007;Hamstra-Bletz & Blote, 1993).…”
Section: Developmental Stages Of Handwriting In Childrenmentioning
confidence: 99%